Colombia : Technical Assistance Report-Report on Sectoral Financial Accounts and Balance Sheets Technical Assistance Mission. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2018)
Colombia is working towards compiling quarterly sectoral accounts and balance sheets to support domestic policymaking by gaining a much deeper understanding of the interrelationship between the real sector accounts and the financial accounts, and the vulnerabilities that may reside in specific sectors as sources for spillovers to other sectors. Sectoral accounts and balance sheets are critical to help detect systemic risks, vulnerabilities, and possible contagion from economic shocks. The authorities continued to acknowledge the additional benefit from work in this area as it moves towards subscription to the IMF's Special Data Dissemination Standard Plus and continued accession negotiations with the Organization for Economic Co-operation and Development. The priority is first on establishing timely annual integrated estimates between the National Administrative Department of Statistics (DANE) and the BRC, followed by quarterly estimates.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: CR; Dane; Estimate; ISCR; Sectoral Account; Colombia